Tropical forest regeneration - Chazdon, Robin (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2012)
Following large-scale human or natural disturbances, the regeneration of tropical forests follows a progression of stages through which forest assemblages gradually become enriched with species and increase in structural and functional complexity. Successional pathways and rates of change vary widely according to the nature of prior land use, the proximity of old-growth forest, and the availability of seed-dispersing fauna. Regenerating forests rapidly accumulate nutrients and carbon in vegetation, litter, and soil, but recovery of species composition may take centuries. Regenerating tropical forests provide essential resources and ecosystem services that support millions of forest-dependent people. When soils have been degraded and seed sources are limited, active reforestation approaches can initiate forest succession and expand forest cover. Reforestation requires an alignment of socio-economic, political, and ecological factors leading to different pathways and quality of reforestation vary across geographic regions.